Posterior acetabular uptake on 18F-fluoride positron emission tomography/computed tomography reveals a putative contrecoup region in patients with femoroacetabular impingement. (30th August 2019) - Oishi, Takayuki; Kobayashi, Naomi; Choe, Hyonmin; Tezuka, Taro; Kobayashi, Daigo; Higashihira, Shota; Inaba, Yutaka
Background and purpose: The pathology of the posterior acetabular lesions, so-called "contrecoup regions", in femorocacetabular impingement (FAI) has not been elucidated fully. 18 F-fluoride positron emission tomography/computed tomography (PET/CT) can visualize abnormal uptake caused by impingement. Therefore, we aimed to evaluate posterior acetabular uptake on PET/CT in FAI patients. Patients and methods: Patients with FAI who underwent 18 F-fluoride PET/CT between October 2014 and October 2016 were retrospectively evaluated. The maximum standardized uptake value (SUVmax ) in the posterior acetabulum was evaluated. The mean SUVmax of FAI with cam morphology (the cam group) was compared with that of FAI with pincer morphology (the pincer group). In addition, the numbers of cases with SUVmax ≥ 6 and SUVmax < 6 in each group were evaluated. The entire study cohort was also grouped according to SUVmax, and the mean α and center edge angles were evaluated. Results: In total, 41 hips were analyzed (34 hips in the cam group and 7 in the pincer group). The mean SUVmax of the cam group (11.2 ± 7.4) was significantly higher than that of the pincer group (4.9 ± 1.9) ( p < 0.01). The incidence of cases with SUVmax ≥ 6 in the cam group was significantly high ( p < 0.01). In the overall cohort, the mean α angle of the SUVmax ≥ 6 group was significantly higher than that of the SUVmax < 6 group ( p < 0.01). Conclusion: Evaluation of posterior acetabular uptake suggests an association between cam morphology and increased posterior acetabular uptake.